Multimodal Diversity of Postmodernist Fiction Text - U. I. Tykha (Vasyl Stefanyk Precarpathian National University, 2016)
The article is devoted to the analysis of structural and functional manifestations of multimodal diversity in postmodernist fiction texts. Multimodality is defined as the coexistence of more than one semiotic mode within a certain context. Multimodal texts feature a diversity of semiotic modes in the communication and development of their narrative. Such experimental texts subvert conventional patterns by introducing various semiotic resources - verbal or non-verbal.